Mitigation of Cyber Security Risk Threats During the Covid-19 Pandemic - Kemian Dai; Ichell Laurant Kawaki; Lintang Dwi Sakti (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2023)
Cyber security mitigation is becoming an increasingly urgent aspect in today's digital era, in response to the threat of theft and disruption to information systems, software and hardware. The Covid-19 pandemic has exacerbated this situation by increasing the chances of success of cyberattacks, as the number and scope of such attacks increases. The impact of increasing levels of cyberattacks is the wider disruption to various sectors. This study aims to investigate cybersecurity issues that arose during the Covid-19 pandemic. Researchers analyzed the current conditions as well as cybercrime acts and various types of cyberattacks carried out during this period. In addition, this research also proposes a practical approach to mitigating the risk of cyber attacks that can be implemented by organizations. It is important for organizations to strengthen the protection of their data and critical assets by implementing a comprehensive cybersecurity approach. The results of this study present various techniques for detecting and avoiding cybercrime threats, even after the pandemic is over. By implementing this approach, damage caused by cyber attacks can be minimized, maintaining the integrity of an organization's data and systems. For future research, it is necessary to carry out further development in the field of cyber security by integrating the latest technologies such as artificial intelligence, blockchain, Internet of Things, and other technologies. In this way, efforts to mitigate cyber attacks can continue to be improved, maintaining the integrity and security of information systems in this ever-growing digital era. This research makes an important contribution to understanding and addressing cyber security issues during the pandemic and provides a foundation for further development in the future.